Preferential Orientation of Crystals Induced by Incorporation of Organic Ligands in Mixed‐Dimensional Hybrid Perovskite Films. Issue 6 (22nd January 2018) - Wang, Rui; Tong, Yu; Manzi, Aurora; Wang, Kun; Fu, Zhendong; Kentzinger, Emmanuel; Feldmann, Jochen; Urban, Alexander S.; Müller‐Buschbaum, Peter; Frielinghaus, Henrich
Abstract: Organic–inorganic perovskites demonstrate great potential for optical applications due to their intriguing optical and optoelectronic properties. Dedicated efforts have been carried out to understand the energy landscape and charge carrier mobilities for perovskite materials. In order to further boost these materials toward large‐scale applications, an alternative "bottom‐up" route for the understanding about correlation between the morphology of high‐quality planar films and their optical properties is essential. Here, mixed‐dimensional bromide‐based hybrid perovskite thin films are prepared from a simple one‐step solution processing route using mixtures of methylammonium bromide (MABr) and octylammonium bromide (OABr). Grazing incidence scattering data statistically reveal that the development of thin‐film morphology as well as crystal orientation depends on the orientation of the OABr crystallites. This study opens up further insight into the morphology of perovskite thin films. In combination, the occurrence of amplified spontaneous emission (ASE) in perovskite films with low ASE thresholds with values approaching 17.8 µJ cm −2 is demonstrated and appears to be closely correlated to the tailored morphology, highlighting its importance for realizing optical gain media. Abstract : Mixed‐dimensional hybrid perovskite thin films are prepared from a simple solution‐processing route. Grazing incidence scattering data statistically reveal that the development of thin‐film morphology as well as crystal orientation depends on the orientation of the organic component. The quality of amplified spontaneous emission in perovskite films is demonstrated and appears to be closely correlated to the tailored morphology, highlighting its importance for realizing optical gain media.